Species distribution and in vitro antifungal susceptibility patterns of Candida - Mondal, S; Mondal, A; Pal, N; Banerjee, P; Kumar, S; Bhargava, D (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.2126/joim.v35i1.8897 Journal of Institute of Medicine, April, 2013; 35:45-49